Exit and Paradise Creek Fluvial Features, 1950 - Curran, Janet H. (ORCID: 000-0002-3899-6275); Williams, Haley B. (USGS Science Data Catalog, 2017)
This dataset presents a delineation of the maximum extent of fluvial occupation detectable from vegetation patterns at Exit and Paradise Creeks in Kenai Fjords National Park, Alaska for 1950 conditions. This comprehensive 1950 surface includes the active braid plain, taken as the suite of wetted channels and largely unvegetated intervening bars (Curran and McTeague, 2011), the inactive braid plain, considered here as vegetated formerly occupied channels and bars still accessible by braiding without substantial bank erosion, and surfaces occupied by former glacier drainage but potentially no longer accessible by braiding. For simplicity, this surface also includes isolated non-fluvial features such as bedrock or moraines stranded within the fluvial features.Limited photo resolution and lack of elevation data precluded differentiating the active and inactive surfaces.